Linking the Variation of Sediment Accumulation Rate to Short Term Sea-Level Change Using Cyclostratigraphy: Case Study of the Lower Berriasian Hemipelagic Sediments in Central Tunisia (Southern Tethys) - Omar, Hamdi; Da Silva, Anne-Christine; Yaich, Chokri (Frontiers in Earth Science, 2021)
High-resolution magnetic susceptibility and % CaCO3 records (5 to 10 cm sampling interval) are used to track astronomical cycles from a Lower Berriasian record from central Tunisia. 622 samples were measured for magnetic susceptibility and carbonate content as paleoclimate proxies for the detection of potential Milankovitch cycles. Elemental data using X-Ray fluorescence analyses was acquired from 19 samples to prove the reliability of the MS signal on recording the past paleoclimatic changes. We performed multiple spectral analyses and statistical techniques on the magnetic susceptibility signal, such as Multi-taper Method, Evolutive Harmonic Analysis, Correlation Coefficient, Time-optimization and Average Spectral Misfit to obtain an optimal astronomical model. The application of these spectral analysis techniques revealed a pervasive dominance of E405-kyr and e100-kyr cycles showing that the climate turnover across the early Berriasian – middle Berriasian seems to had been governed by the long and short orbital eccentricity cycles. The identification of Milankovitch cycles in the record also allowed to propose a floating astronomical timescale of the studied section, with ~4 long eccentricity cycles (E405) extracted, which points to a duration estimate of ~1.6 Myr with an average sediment accumulation rate (SAR, after compaction) of 2.77 cm/kyr. The inferred floating ATS was tuned to the La2004 astronomical solution. In addition, we applied the DYNOT and ρ1 methods for seal-level change modeling to reconstruct a local eustatic profile which matches the previously published local and global eustatic charts.